Examination of the Life Habits of Preschool Children Based on Their Screen Use Patterns - Cakiroglu, Tugba Yazici; Sapsaglam, Ozkan (MDPI, 2024)
Children who open their eyes to a digital world begin interacting with screens in the early years of life. The interaction between screens and children starts from the very first moments of life and intensifies over time. The aim of this study is to examine the effects of screen use patterns on the life habits of preschool children. In this context, the relationships between problematic media use, eating habits, and self-care skills among preschool children are analyzed from various perspectives. Structured according to a mixed-methods research approach, this study employs both qualitative and quantitative research designs. The study group consists of 582 children continuing their education in preschool institutions across seven different regions and nine different provinces in Turkey, along with 20 of their parents. Random and non-random sampling methods were used to form the study group. Quantitative data were collected using the Problematic Media Use Measure, Children's Eating Behavior Inventory, and Preschool Children (36-72 months) Self-Care Skills Scale-Teacher Form, while qualitative data were gathered through a semi-structured parent interview form. The study results indicate that problematic media use and eating behaviors significantly vary according to the screen time of children, with an increase in problematic media use linked to a rise in negative eating behaviors. Parents are found to perceive the use of media devices during mealtime as a necessity, thus employing them, and believe that their children's social behaviors are shaped according to screen content.
Keywords: early childhood; screen use; life habits; eating behavior; self-care; TELEVISION EXPOSURE; MEMORY PERFORMANCE; SLEEP; MEDIA; ASSOCIATIONS; COMPUTER; GAME; Pediatrics